THE EFFECT OF METABOLIC DISORDER RISK ON THE VARIABILITY OF BIOCHEMICAL PARAMETERS IN COWS' BLOOD AND MILK REGARDING THE SAMPLING MONTH - Poljak, Franjo; Šperanda, Marcela; Đidara, Mislav; Gantner, Ranko; Brka, Muhamed; Gantner, Vesna (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Aiming the determination the variability of biochemical parameters in blood plasma and milk of Holstein cows regarding the metabolic disorder risk (based on F/P ratio classes) separately for each sampling month (May, June, July), blood and milk were sampled from 75 high-yielding Holsteins reared on a dairy cattle farm in East Croatia. The metabolic disorder risk was defined concerning the daily fat/protein ratio (F/P) obtained from test-day records (F/P < 1.1 indicating acidosis risk; F/P in [1.1, 1.5], the normal status of an animal; F/P > 1.5, indicating ketosis risk).The conducted analysis showed variability in the values of the biochemical parameters in both blood plasma and milk due to metabolic disorder risk and month of sampling. Accordingly, when different metabolites are used as an indicator of the metabolic disorder risk, correction for the systematic effects (stage of lactation and parity, sampling month) should be applied.